Psicanálise e uso de drogas: articulações com a Redução de Danos no Sistema Único de Saúde (SUS) - Winning, Renata da Silva (2018)
The relation of the human being with drugs has not always been protected by the State. Since the nineteenth century, paradigmatic changes have occurred in relation to drugs that culminated in the creation of specific policies to problems related to its consumption. The theoretical study developed here brought articulations between the psychoanalytic clinic and the harm reduction strategy by analysing its implantation in the Unified Health System (SUS). From that point, it was made a dialogue between the psychoanalytic propositions concerning the drug compulsive use phenomenon and its treatment as well as possible approximations with the harm reduction logic. We have debated, throughout this study, in which ways the discursive turns formalized by Jacques Lacan accompanied the historical, political and economic changes involving the use of drugs; we analysed the proposal of harm reduction; developed questions that guide psychoanalytic clinic; illustrated the divergences between the treatment direction within the institutional context concerning the harm reduction and abstinence simultaneously to the pre-condition and treatment aim. By presenting a logic that considers the autonomy, the bond and the general life context as the motto of its actions, disregarding the idea that drugs is the main problem to be treated and making abstinence more flexible as an ideal of cure. The strategies of harm reduction favor articulations with the psychoanalytic work, that, in turn, contributes to the particularity of the listening clinic and intervention from the subject of the unconscious